Elastic and inelastic scattering for the B 10 + Ni 58 system at near-barrier energies - Scarduelli, V.; Crema, E.; Guimarães, V.; Abriola, Daniel Hugo; Arazi, Andres; de Barbará, Ezequiel; Capurro, Oscar Ángel; Cardona, Maria Angelica; Gallardo, J.; Hojman, Daniel Leonardo; Martí, Guillermo Virginio; Pacheco, Alberto Jorge; et al. (American Physical Society, 2017)
Fil: Scarduelli, V.. Universidade de Sao Paulo; Brasil